The Effectiveness of a Learning Program on Creative Problem Solving Model (CPS) in Developing Mathematical Skills for 10th Grade Students - Obeidat, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏ Alya Rachid (Journal of Educational and Psychological Sciences, 2018)
This study aims to investigate the effectiveness of a Learning program based on a creative problem solving model (CPS) in developing mathematical power for 10th grade students. To achieve this goal, the 15-question mathematical strength test was designed to measure the tribal and post-performance of the students in sports power. The study sample consisted of (40) students randomly divided into two groups: the experimental consisted of (20) students studied the unit using the program model of creative solution to problems, and the control consisted of (20) students studied using the regular program. To achieve study object (ANCOVA 2X3) in which eta squared was obtained. The results of the study showed a statistically significant difference (0,05) between the average scores of the students in the two groups of study in the sports force test. The experiment obtained a general mean (4.18) compared to the control of the control of the general average (3.62) and the difference in favor of the students in the experimental group. In the light of the results, a set of recommendations and proposals were presented to enhance the use of the CPS model in the teaching of mathematics for the students of the tenth grade, through the implementation of training courses for the teachers of mathematics on the application of the solution model of the problems of teaching.